2019
DOI: 10.5551/jat.rv17032
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disordered Breathing and Cardiovascular Diseases

Abstract: Sleep disordered breathing (SDB), which causes sleep deprivation, intermittent hypoxia, and negative intrathoracic pressure swings, can be accompanied by other harmful pathophysiologies relating to cardiovascular diseases (CVD), including sudden death, atrial fibrillation, stroke, and coronary artery disease leading to heart failure. Continuous positive airway pressure (CPAP) therapy for SDB has been reported to provide favorable effects such as lowered systemic blood pressure and improved endothelial function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 110 publications
0
37
0
Order By: Relevance
“…Although a recent randomized controlled trial in Japanese hemodialysis patients suggested that oral VDRA did not reduce the risk of cardiovascular events, including sudden death 44) , the proportion of sudden death among all cardiovascular events is small (18 of 188), and the effect of VDRA on different genders is death were not evaluated. In particular, serum potassium levels, which could be a strong contributor of sudden death, other dialysis parameters, except for dialysis session length and Kt/V (e.g., blood flow rate and ultrafiltration rate), nutritional parameters, except albumin and body mass index, echocardiographic, and electrocardiographic data (e.g., ejection fraction, left ventricular hypertrophy, and QT interval), cardiac biomarker data, (e.g., troponins and atrial/brain natriuretic peptides), and data of commodity such as sleep apnea syndrome, which is one of the important causes of sudden death 51) , and medical treatment (e.g., antiplatelet agents and -blockers) were missing. Finally, the detailed timing of sudden death (i.e., if deaths occurred in the hours before or after dialysis) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent randomized controlled trial in Japanese hemodialysis patients suggested that oral VDRA did not reduce the risk of cardiovascular events, including sudden death 44) , the proportion of sudden death among all cardiovascular events is small (18 of 188), and the effect of VDRA on different genders is death were not evaluated. In particular, serum potassium levels, which could be a strong contributor of sudden death, other dialysis parameters, except for dialysis session length and Kt/V (e.g., blood flow rate and ultrafiltration rate), nutritional parameters, except albumin and body mass index, echocardiographic, and electrocardiographic data (e.g., ejection fraction, left ventricular hypertrophy, and QT interval), cardiac biomarker data, (e.g., troponins and atrial/brain natriuretic peptides), and data of commodity such as sleep apnea syndrome, which is one of the important causes of sudden death 51) , and medical treatment (e.g., antiplatelet agents and -blockers) were missing. Finally, the detailed timing of sudden death (i.e., if deaths occurred in the hours before or after dialysis) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricaemia was defined as regular usage of antihyperuricemic agents or serum uric acid levels of over 7 mg/dL 19. Sleep-disordered breathing (SDB) was defined as apnoea–hypopnoea index of >5 times/hour, and included both central and obstructive SDB, determined by a portable sleep monitor, polysomnography and/or from medical records 20–22. Chronic obstructive pulmonary disease was defined as forced expiratory volume in one second/forced vital capacity of <70% by spirometry according to the Global Initiative for Chronic Obstructive Lung Disease, the American Thoracic Society/European Respiratory Society guidelines, and/or from medical records 23.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between HF and sleep is, again, likely bi-directional. Sleep disturbance is associated with several cardiovascular disease risk factors, and cardiovascular disease, in addition to higher sympathetic activity [153][154][155]. With this considered, sleep disturbance may lie along the causal pathway for forms of HF, or potentially exacerbate the condition.…”
Section: Heart Failurementioning
confidence: 99%